0186 Made from scratch – an apprentice led development for in-house moulage skills. (2nd November 2015) - Charlton, Olivia; Riby, Stuart; Graby, Matthew; Gay, Christopher
Abstract : Background/context: Moulage was an area that needed development at HILS, our knowledge was very limited and we had little time to practice. With the appointment of an apprentice simulation technician we were able to branch into areas that we couldn't previously – in-house moulage being one of these. Our apprentice technician was tasked with this development and pioneered our journey from having no moulage activity to having our own in-house moulage skills course. Description of innovation or topic: Our apprentice expressed an interest in moulage skills and through a mixture of formal training (Inspire, Trauma FX) and research our apprentice was able to grow an in depth knowledge of moulage and special effects within healthcare. Being high in confidence and proud to have ownership of a section of the teams services our apprentice began to have ambitious plans such as developing a HILS in-house moulage skills course. Improvements/outcomes: Technical team member highly skilled is in medical moulage skills. Every course that now runs in HILS is offered the option to have moulage in their scenarios. An extensive stock of specialist makeup/moulage materials. The development of an in-house course. The 'Introduction to Moulage' course has had a successful pilot and is now due to run bi-annually in HILS. Enhanced fidelity for our scenarios and courses which in turn helps to improve participant engagement. Take home messages: Addressing opportunities in your team's skillset and finding solutions can advance your centre by using individuals strengths and enthusiasm to build new skills. Moulage can be a key element in simulation and can improve candidate engagement in scenarios. There are fantastic training opportunities to help your staff become proficient in moulage skills on humans or manikins. Empowering staff and giving them responsibility to improve areas of the team can lead to extremely positive outcomes.